SISTEM INFORMASI PENGOLAHAN PEMBIMBING AKADEMIK JURUSAN ILMU KOMPUTER - Anie Rose Irawati; Dwi Sakethi; Dimas Wisnu Anggoro (Jurnal Komputasi, 2014)
The academic supervisor help collagers to finish their study well and efficient depends on their condition and potential. The allocation of academic supervisor in computer science major was done manually, Â it makes data processing become over late. This study, develop a web based system to help determine the academic supervisor for each collager, and to represent it in a graph. This system is developed in PHP programming language. The system outputs are collegers data and their academic supervisor, and the graph of collegers data for each supervisor. The system also represent the data result in a format of SK proposed format.The system development use prototype method. The advantage of prototype method is the system can be Â develop as expected by user. First prototype produces some functions such as login, lecture and colleger data input, clear data academic supervisor, edit data academic supervisor, and devided colleger data for each supervisor. Second prototype produce some addition function such as print complete supervisor data, print supervisor data, and show supervisor data graph.Keyword : Academic Supervisor, Prototype Method